Contract farming and pro-environmental behavior: insights from beef cattle farmers - Liang, Yuan; Zhang, Peihang; Bi, Wentai; Qi, Qi; Xie, Fengjie (Frontiers in Sustainable Food Systems, 2025)
IntroductionFacilitating and motivating farmers to adopt standardized pro-environmental production technologies serve as a solution to agricultural surface pollution. Moreover, this approach represents a crucial strategy for promoting low-carbon sustainable development in the farming sector. However, despite the potential of pro-environmental production techniques to facilitate this objective, the adoption rate among Chinese beef farmers remains suboptimal.MethodsThis study empirically examines the influence and mechanisms of contract farming on farmers’ pro-environmental behaviors by considering survey data from Chinese beef cattle farmers analyzed using an ordered probit model. To enhance our understanding, we explore the effects of contract farming on various pro-environmental production technologies under different constraints.ResultsThe findings reveal that contract farming significantly fosters pro-environmental behaviors among farmers, particularly through enhanced participation in resource-providing contracts. Anticipated economic and ecological benefits and access to information have emerged as critical mediators of the relationship between contract farming and pro-environmental behaviors. Heterogeneity analysis indicates that the impact of contract farming on the adoption of diverse pro-environmental production technologies varies among farmers. Additionally, contract farming exhibits differential effects on the pro-environmental behaviors of various farmer cohorts, influenced by factors such as specific investment, farm size, training frequency, and environmental regulations.DiscussionThis study explores the role of farmers’ participation in contract farming in promoting pro-environmental behaviors amidst environmental challenges in the context of beef cattle farming. Due to limitations in data availability and the geographical scope of the study, we have not included a more detailed discussion of the mechanisms or specific implications for other relevant stakeholders. Overall, the findings of this study not only provide new insights into strategies to encourage farmers to engage in pro-environmental behaviors, but also entry points for further research to enhance current environmental policies and promoting the large-scale development of the beef cattle industry. The results of this study indicate that the promotion of pro-environmental behaviors among farmers can be achieved by encouraging them to participate in contract farming. This approach aims to optimize and improve current environmental policies, thereby facilitating the joint promotion of scale and specialization in the beef cattle industry.